(untitled) (Altre Modernità, 2025)
Tender is the Flesh (originale title: Cadáver Exquisito is a dystopian novel written in 2017. Argentinian author Agustina Bazterrica imagined a world where cannibalism is legal but disguised. After a pandemic that led to the extermination of animals, society began the “transition” to the “special meat”: human meat. The first “specimens” to be selected to be “bred” came from marginalized and impoverished communities. Based on a strong manipulation of language, a deep socio-political process of dehumanization convinced public opinion that human “heads” (deprived not only of their rights but also of their voices, since their vocal cords are cut out) are to be considered as edible animals. Also brutally reflecting on the current meat production system, Tender Is the Flesh satirically shows the extremes to which hegemonic capitalism can go, marginalizing and oppressing both environment and otherness (women, the poor, animals, etc.). Through the story of Marcos and his abused “female head” Jasmine (Jasmín in the original text), Bazterrica shows us that “the domination of nature by man stems from the very real domination of human by human” (Bookchin Ecology 1). The article analyzes four main themes: 1) the processes that lead to the biopolitical hierarchies of bodies, exposing society’s privileges, double standards, structural injustice, and mechanisms of exploitation, 2) the influence of racism, social status, patriarchy, speciesism, and economic factors in the construction and repression of otherness, 3) the use of language and (forced) silence in real and fictional forms of cannibalistic thanatopolitics, and 4) the Animal Studies and ecocritical perspectives within the book.